PROBLEMATIKA SDM PENGAWAS PEMILU DAN PENTINGNYA PENGAWAS PARTISIPATIF MENGHADAPI PEMILU SERENTAK TAHUN 2024 - Marzuki, H.M. Wasikin (Bawaslu Provinsi Jawa Barat, 2021)
The incompatibility of the number of election supervisory personnel with a heavy workload is a human resource (HR) problem that must be addressed in the run-up to the 2024 General Elections and Simultaneous Elections. In addition, the room for evaluating the institutional governance of election organizers through the revision of the Election Law has been closed. This issue is certainly a challenge that Bawaslu must address by improving the quality of human resources and expanding the role of the community so that they are more actively participating in election supervision to create an honest, fair, and quality electoral process. Participatory supervision can be a solution to Bawaslu's problems related to the incompatibility of human resources in facing the 2024 General Elections and Simultaneous Elections.